Understanding the Bengal Muslims : interpretative essays - Ahmed, Rafiuddin, 1941- (New Delhi : Oxford University Press, 2001)
Contributed articles.
the Jama't-i-Islami in Bangladesh / Enayetur Rahim.
Includes bibliographical references and index.
BIED
Complimentary copy from BIED
Keywords: Muslims -- India -- Bengal -- History; Bengal (India) -- History